Photoconductive Semiconductor Switches: Materials, Physics, and Applications - Vincent Meyers; Lars Voss; Jack D. Flicker; Luciano Garcia Rodriguez; Harold P. Hjalmarson; Jane Lehr; Nicolas Gonzalez; Gregory Pickrell; Soroush Ghandiparsi; Robert Kaplar (Applied Sciences)
Photoconductive semiconductor switching (PCSS) devices have unique characteristics to address the growing need for electrically isolated, optically gated, picosecond-scale jitter devices capable of operating at high voltage, current, and frequency. The state of the art in material selection, doping, triggering, and system integration in PCSSs is presented. The material properties and doping considerations of GaN, GaAs, SiC, diamond, and β-Ga2O3 in the fabrication of PCSS devices are discussed. A review of the current understanding of the physics of the high-gain mode known as lock-on is presented.